The problem of hardiness and anti-social behaviour - N.A., Aldabergenov (Opción, 2019)
The purpose of the study is to determine the level of the hardiness of young people who committed a crime and identify factors affecting their hardiness via a synthesis of scientific material and practical experience together with methods for finding a relationship between productive and factor variables. The obtained results allowed us to build a model of the influence of various factors on human hardiness. In conclusion, the components of hardiness, mainly developed in childhood, but with the help of psychological techniques can be developed in adolescence and at a young age.